BREAST CANCER TRENDS IN A NIGERIAN POPULATION: AN ANALYSIS OF CANCER REGISTRY DATA: Life Science-Pathology - ABIODUN FMCPATH, AFOLAYAN; OLATUNDE FWACS, OLAOYE; MICHAEL FWACS, ADESINA; RAKIYA FMCOG, SAIDU (International Journal of Life Science and Pharma Research, 2012)
Background: - Worldwide, breast cancer is the commonest cancer in women and characterized by regional variations and late clinical presentation in low and middle income countries including Nigeria. Objectives – The purpose of this communication is to highlight the trends of breast cancer in a Nigerian population in a way to assess the effectiveness of various control measures including mammography instituted to control the disease. Materials and Methods – Data on new cases of breast cancer registered annually at the cancer registry of the hospital over a period of 10-years were obtained and analyzed. Cancer reporting was voluntary hence data were collected by active search. Sources of information included pathology laboratories, clinics, and wards e.t.c. Information abstracted on both patients and cancer included age, sex, bases of diagnosis, incidence date, topography, (primary sites), and morphology among others. Breast cancer was coded as C50, using International Classification of Diseases 10th edition (ICD 10th) of World Health Organization. Results – There were 568 new cases of breast cancer registered at the cancer registry during the 10-year period, comprising of 7(12.23%) males and 561(98.77%) females. The youngest patient aged 18 years while the oldest was 93 years and the peak age of incidence was the 5 th decade. Incidence of breast cancer in male was low and occurred at a relatively older age group. We observed steady rise in cases of breast cancer at our centre. Conclusion – The steady rise in breast cancer cases in the study population is an indication of inadequate or ineffective control measures to curtail the disease or due to diversion of global attention to HIV/AIDS and tuberculosis in the country. Therefore there is urgent need to step up activities through non-governmental agency to promote advocacy, national policy on training of personnel for clinical and self-breast examination, and nationwide screening program (mammography) in order to enhance early detection, control the upward trends and reduce the mortality rate of breast cancer